The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1073/pnas.71.10.3961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Near-Ultraviolet and Visible Light on Mammalian Cells in Culture II. Formation of Toxic Photoproducts in Tissue Culture Medium by Blacklight

Abstract: Near-ultraviolet radiation was found to be lethal for mammalian cells in Dulbecco's modified Eagle's medium without serum or phenol red. Irradiation of the cells with near-ultraviolet light while the cells were in phosphate-buffered-saline abolished the lethal effect. When only the medium was irradiated followed by the addition of unirradiated cells and serum, the cells were still killed. The photoactive components of the medium for this effect were riboflavin, tryptophan, and tyrosine. When riboflavin was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 34 publications
4
49
0
1
Order By: Relevance
“…Work by Griffin et al [35] suggested that just 3 h exposure of riboflavin-containing medium to bench-top levels of cold white fluorescent light could produce significant toxicity in a leukaemic cell line. The principal mechanism of phototoxicity is thought to involve the generation of "O # and probable subsequent oxidation of the amino acids tryptophan and tyrosine [35,36]. It has since been demonstrated that fluorescent light may cause a build up of toxic H # O # levels in DMEM or RPMI-1640 medium, both of which contain riboflavin [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Work by Griffin et al [35] suggested that just 3 h exposure of riboflavin-containing medium to bench-top levels of cold white fluorescent light could produce significant toxicity in a leukaemic cell line. The principal mechanism of phototoxicity is thought to involve the generation of "O # and probable subsequent oxidation of the amino acids tryptophan and tyrosine [35,36]. It has since been demonstrated that fluorescent light may cause a build up of toxic H # O # levels in DMEM or RPMI-1640 medium, both of which contain riboflavin [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to state that in all experiments carried out on osteoblasts in this study, culture medium was replaced with phosphate buffered saline (PBS) for the duration of HINS-light exposure due to possible generation of ROS in the culture medium. Cell viability has been shown to be significantly reduced by exposure to visible and near-UV radiation when exposed in culture medium compared to PBS (Stoien and Wang, 1974;Smith, 2009). The main component of culture medium responsible for ROS generation has been shown to be riboflavin, with tryptophan, tyrosine, pyridoxine and folic acid all enhancing the effect (Grzelak et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…S3). Importantly, our approach allows arbitrarily thick tissues to be fabricated, because the matrix does not require UV curing (19), which has a low penetration depth in tissue (20) and can be readily expanded to other biomaterials, including fibrin and hyaluronic acid (SI Appendix, Fig. S4).…”
mentioning
confidence: 99%